2006
DOI: 10.1007/s11104-006-0037-9
|View full text |Cite
|
Sign up to set email alerts
|

Turfgrass (Cynodon dactylon L.) sod production on sandy soils: I. Effects of irrigation and fertiliser regimes on growth and quality

Abstract: The effects on growth, quality and N uptake by turfgrass (Cynodon dactylon L.) during sod production of four fertiliser types applied at three application rates (100, 200 or 300 kg N ha )1 per 'crop') under two irrigation treatments (70% and 140% daily replacement of pan evaporation) were investigated. The fertiliser types were: water-soluble (predominately NH 4 NO 3 ), control-release, pelletised poultry manure, and pelletised biosolids; and the experiment was conducted on a sandy soil in a Mediterranean-type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 33 publications
(30 reference statements)
1
25
0
Order By: Relevance
“…managed as golf course rough (Qian et al, 2010), although the effect disappeared by the fourth year after establishment. A study of couch grass (Cynodon dactylon L.) grown for sod production tested the effects of both N fertilization and irrigation (Barton, Wan, & Colmer, 2006); fertilization increased total biomass production by up to tenfold, with production of clippings and roots showing the strongest response, while excessive irrigation decreased clippings production, and in some cases standing root biomass as well. While limited, these results offer preliminary evidence that turfgrass can respond strongly to management.…”
Section: Introductionmentioning
confidence: 99%
“…managed as golf course rough (Qian et al, 2010), although the effect disappeared by the fourth year after establishment. A study of couch grass (Cynodon dactylon L.) grown for sod production tested the effects of both N fertilization and irrigation (Barton, Wan, & Colmer, 2006); fertilization increased total biomass production by up to tenfold, with production of clippings and roots showing the strongest response, while excessive irrigation decreased clippings production, and in some cases standing root biomass as well. While limited, these results offer preliminary evidence that turfgrass can respond strongly to management.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, in Cynodon dactylon L. sod, Barton et al (2006) indicated that chemical N fertilizers doubled shoot growth and improved turfgrass greenness in comparison with plots receiving pelletized poultry manure or biosolids.…”
Section: Downloaded By [Rutgers University] At 13:55 06 April 2015mentioning
confidence: 97%
“…Despite the existence of several studies on the effects of animal waste and bio-solids on turfgrasses, limited published data are available regarding the effects of using composted chicken (Gallus gallus) manure as a topdressing material. Barton et al (2006) indicated that water-soluble and control-release chemical N fertilizers produced better shoot growth and color than pelletized poultry manure in Cynodon dactylon sod. The nitrogen use efficiency of the poultry manure was also much lower than that of inorganic fertilizers.…”
Section: Introductionmentioning
confidence: 99%
“…In both cases, by adjusting N fertilizer rates and water supply, turfgrass visual color and quality will be able to be maintained. Similarly, Barton et al [24] also recommend that under the low irrigation treatment, inorganic N fertilizers applied at 200-300 kg N/ha were adequate for the production of turfgrass sod. Many studies have considered the effects of various N fertilization rates on quality, but very few have included the practice of returning grass clippings.…”
Section: Turfgrass Qualitymentioning
confidence: 99%